Influence of innovation on customer satisfaction: a case of customers of Safaricom Plc - Ogogo, S. A. (Strathmore University, 2023)
Businesses today operate in a competitive environment and therefore they need to ensure they keep their customers satisfied. The competition is not just local but global, making organizations rethink about strategies for customer satisfaction. One such strategy is innovative strategies. The telecommunication industry in Kenya has become competitive and firms in this sector have been forced to come up with new and improved ideas to better their services and products so as to deliver customer satisfaction. Previous studies have presented conceptual, contextual, and methodological gaps which this study sought to address by determining the influence of innovation on customer satisfaction for customers of Safaricom Plc. The specific objectives of the study were to establish the influence of product innovation on customer satisfaction for customers of Safaricom Plc, to establish the influence of process innovation on customer satisfaction for customers of Safaricom Plc and to establish the influence of marketing innovation on customer satisfaction for customers of Safaricom Plc. This study was informed by two theories namely: Diffusion of Innovation Theory and Expectancy disconfirmation Theory. The study employed descriptive cross -sectional research design and made use of Krejcie and Morgan table and 5% level of precision or margin of error to arrive at a sample size of 385 respondents to whom structured questionnaire was administered. The data collected was purely quantitative, thus SPSS aided the analysis. The analysis involved the use of descriptive and inferential statistics. The results were displayed using tables, charts, and bars. The findings revealed that the variance in the dependent variable was explained by the model. The coefficient of determination indicated that the independent variables used in this study of product innovation, process innovation and marketing innovation were jointly responsible for variation in customer satisfaction for customers of Safaricom Plc. The remaining percentage of the expected variation in customer satisfaction for customers of Safaricom Plc. was accounted for by other factors which were not part of the current model. The study found that the model adopted in this study was statistically significant in explaining the influence of innovation (product innovation, process innovation, and marketing innovation) on customer satisfaction for customers of Safaricom Plc. In terms of the influence of each innovation, the study established a positive and significant relationship between product innovation and customer satisfaction, a positive and significant relationship between process innovation and customer satisfaction, and a positive and significant relationship between marketing innovation and customer satisfaction. The findings led to the conclusion that various forms of innovations used in this study - product, process, and marketing innovation each have a significant and positive influence on customer satisfaction for customers of Safaricom Plc. The study thus recommends that the management of Safaricom Plc should continue to prioritize and invest in innovation as a central component of its business strategy. The management should also dedicate resources to research and development, fostering a culture of innovation within the organization, and regularly seeking feedback from customers to understand their needs and preferences. The study was limited by use of a small sample size of customers within Nairobi County, and relied solely on self-reported measures, presenting a risk of response bias or social desirability bias. Only three innovation types were used in the study. Future studies could address these limitations.
Full- text thesis